2018
DOI: 10.3390/geriatrics3030055
|View full text |Cite
|
Sign up to set email alerts
|

Orthogeriatrics and Hip Fracture Care in the UK: Factors Driving Change to More Integrated Models of Care

Abstract: In the United Kingdom (UK), approximately 80,000 hip fractures each year result in an estimated annual cost of two billion pounds in direct healthcare costs alone. Various models of care exist for collaboration between orthopaedic surgeons and geriatricians in response to the complex medical, rehabilitation, and social needs of this patient group. Mounting evidence suggests that more integrated models of orthogeriatric care result in superior quality of care indicators and clinical outcomes. Clinical governanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Multidisciplinary team approach with medical optimisation, early surgical intervention followed by rehabilitation is considered the ideal treatment for older people with significant spinal injuries. Ortho-geriatric care has emerged as a collaborative care model between geriatricians and orthopaedic surgeons for older adults hospitalised with hip fracture 4 . A national survey has shown that increasing ortho-geriatrician time spent per patient from 1.5 to 4 hours, resulted in reduction in time to theatre, with an overall 3.4% decrease in 30day mortality 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Multidisciplinary team approach with medical optimisation, early surgical intervention followed by rehabilitation is considered the ideal treatment for older people with significant spinal injuries. Ortho-geriatric care has emerged as a collaborative care model between geriatricians and orthopaedic surgeons for older adults hospitalised with hip fracture 4 . A national survey has shown that increasing ortho-geriatrician time spent per patient from 1.5 to 4 hours, resulted in reduction in time to theatre, with an overall 3.4% decrease in 30day mortality 5 .…”
Section: Discussionmentioning
confidence: 99%
“…These are all factors that account for the rise in the number of the ageing population across the globe, as their standard of living is improved, prolonging their length of stay as active or thriving members of the world's population. Taking into view some common problems that affect the elderly, several reforms have been made in the health system to fend for the needs of the aged, for example, the guidelines put in place by the National Health Service of the United Kingdom towards the care and surgery of aged patients with hip fractures [13]. A multidisciplinary approach to caring for older adults is highly recommended and in the United Kingdom, national guidelines have been published in this regard.…”
Section: Geriatric Carementioning
confidence: 99%
“…This has been recognised previously in patients sustaining hip fractures and has given rise to a drive for optimisation of these patients in the form of national guidelines and the Best Practice Tariff (BPT) for hip fractures [1] . Initiatives such as a comprehensive geriatric assessment prior to surgery and time to surgery within 36 hours have improved care and reduced mortality [2] .…”
Section: Introductionmentioning
confidence: 99%